The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.14210/bjast.v17n2.p7-15
|View full text |Cite
|
Sign up to set email alerts
|

Abundância das larvas de Porcellanidae (Decapoda, Anomura) no meroplâncton do estuário do Rio Caeté, estuário amazônico brasileiro

Abstract: The life cycle of these species includes only two zoeal stages, which are distinctive by their very elongate rostral and posterolateral carapace spines, and are commonly found in estuarine meroplanktonic samples. The present study provides information about the abundance of porcellanid larvae at an estuarine system in the Amazon coastal zone, aiming to understand their distribution in relation to some physicochemical variables: seasonal, diel, tidal and lunar cycles, temperature and salinity. Samples were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Accordingly, a previous study on holoplanktonic luciferid shrimps (Melo et al, 2014) showed that their abundance decreased substantially along a gradient from the coast towards offshore waters, on the North Brazilian Shelf. Other studies of decapods in the study area were conducted by Cavalcante et al (2012), de Oliveira et al (2012), Carvalho et al (2013) and Nóbrega et al (2014). Nevertheless, most of these studies were carried out on the continental shelf close to the Amazon River mouth, and there are few published studies in oceanic areas near the shelf break and slope (Melo et al, 2014) or following the ARP (Calef and Grice, 1967;Conroy et al, 2016Conroy et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a previous study on holoplanktonic luciferid shrimps (Melo et al, 2014) showed that their abundance decreased substantially along a gradient from the coast towards offshore waters, on the North Brazilian Shelf. Other studies of decapods in the study area were conducted by Cavalcante et al (2012), de Oliveira et al (2012), Carvalho et al (2013) and Nóbrega et al (2014). Nevertheless, most of these studies were carried out on the continental shelf close to the Amazon River mouth, and there are few published studies in oceanic areas near the shelf break and slope (Melo et al, 2014) or following the ARP (Calef and Grice, 1967;Conroy et al, 2016Conroy et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests its characterization as a cosmopolitan and eurytopic species, which allows its wide distribution in Sepetiba Bay and denotes its high ecological value. In addition, other studies have reported the euryhaline character in the larval (Carvalho et al, 2013) and adult forms (Coelho, 1963(Coelho, , 1964, eurythermic characteristics (Stilman & Somero, 2000), and the use of different strategies by the species. Among those strategies, it is worth mentioning the escape mechanism (Wasson & Lyon, 2005) and the commensally interaction between post-planktonic stages and gastropod Crucibulum spinosum (Sowerby, 1824), reducing the risk of desiccation at low tides and minimizing the pressure by predation during high tides (Campos-Gonzáles & Macías-Chávez, 1987).…”
Section: Discussionmentioning
confidence: 97%